2012
DOI: 10.3324/haematol.2011.061093
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for survivin in erythroblast enucleation

Abstract: The online version of this article has a Supplementary Appendix. BackgroundNucleus free red blood cells are unique to mammals. During their terminal stage of differentiation, mammalian erythroblasts exit the cell cycle and enucleate. We previously found that survivin, a member of the chromosomal passenger complex that is required for cytokinesis, is highly expressed in late non-dividing cells. The role of survivin in enucleating erythroblasts is not known. Design and MethodsIn order to identify the role of sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…Several lines of evidence support the hypothesis that formation of cytoplasmic vesicles and autophagic vacuoles contributes to enucleation [4,5]. Recently, Keerthivasan et al [4,5] showed that vesicle trafficking, in particular the formation and movement of vacuoles at the junction of the nucleus and the cytoplasm, is a critical component of mammalian erythroblast enucleation. There is likewise evidence supporting a link between autophagy and vesicle trafficking [43].…”
Section: Discussionmentioning
confidence: 90%
“…Several lines of evidence support the hypothesis that formation of cytoplasmic vesicles and autophagic vacuoles contributes to enucleation [4,5]. Recently, Keerthivasan et al [4,5] showed that vesicle trafficking, in particular the formation and movement of vacuoles at the junction of the nucleus and the cytoplasm, is a critical component of mammalian erythroblast enucleation. There is likewise evidence supporting a link between autophagy and vesicle trafficking [43].…”
Section: Discussionmentioning
confidence: 90%
“…Throughout terminal erythropoiesis, erythroblasts undergo gradual nuclear condensation that is associated with decreased cell size. This is followed by the extrusion of the pycnotic nucleus in the final stage of terminal differentiation that involves a highly regulated asymmetric cell division processes (Ji et al, 2008; Keerthivasan et al, 2010; Ji et al, 2011; Zhang et al, 2011; Keerthivasan et al, 2012; Konstantinidis et al, 2012; Ubukawa et al., 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed that multiple signaling pathways are involved in the generation of enucleated erythroid cells. 6,7 These include histone deacetylation, 8,9 actin cytoskeleton, [10][11][12][13] cytokinesis, 14,15 cell-matrix interactions, 16 specific microRNAs 17 and vesicle trafficking. 18 Many of these studies used a mouse fetal liver erythroblast culture system, which makes it possible to analyze erythroid cell differentiation and enucleation both quantitatively and step by step.…”
Section: Introductionmentioning
confidence: 99%